The Use of Talking Chips Technique to Improve Students’ Speaking Skill - Intan Mahardika Kusumastuti (Pancaran Pendidikan, 2018)
This research aimed to identify: (1) how Talking Chips technique can be implemented in improving the students’ speaking skill and (2) how the implementation of Talking Chips technique can improve the class atmosphere. It was a Classroom Action Research conducted to students in class VIII H of SMP Al-Islam 1 Surakarta in the academic year of 2015/2016. The data were collected through observational and non-observational technique. The data collected were analyzed by using qualitative data and desriptive statistics. By implementing this technique, the findings of this research indicate that the students’ speaking skill which covers comprehension, fluency, grammar, pronunciation, and vocabulary improve. The use of this technique can also improve the class atmosphere due to the activeness of the students in the learning activity. It facilitates the students to participate in the speaking activity equally by using chips.